1999
DOI: 10.1055/s-1999-9464
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prior Activity Upon Inspiratory Muscle Strength in Rowers and Non-Rowers

Abstract: The aim of this study was to investigate whether a 'warm-up' phenomenon in the strength of the inspiratory muscles exists, and, under this assumption, whether whole body warm-up protocols or a specific respiratory warm-up is more effective in this respect. Eleven club level rowers performed a rowing warm-up, and twelve university students performed a general cycling warm-up. Both groups also performed a specific respiratory warm-up. Inspiratory muscle strength (Mueller manoeuvre) and lung function (flow-volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 18 publications
8
30
0
Order By: Relevance
“…2006;Volianitis et al 1999;Volianitis et al 2001) and similar increases have also been observed in the maximal rate of inspiratory pressure development (Lin et al 2007;Tong and Fu. 2006).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…2006;Volianitis et al 1999;Volianitis et al 2001) and similar increases have also been observed in the maximal rate of inspiratory pressure development (Lin et al 2007;Tong and Fu. 2006).…”
Section: Discussionsupporting
confidence: 72%
“…An inspiratory muscle warm-up (IMW) comprising inspiratory pressure-threshold loading increases inspiratory muscle strength and the maximum rate of inspiratory pressure development by 10% (Hawkes et al 2007;Lin et al 2007;Lomax et al 2011;Ross et al 2007;Tong and Fu. 2006;Volianitis et al 1999;Volianitis et al 2001). Furthermore, the addition of an IMW to a whole-body active warm-up increased the distance completed during exhaustive intermittent running (Lin et al 2007;Lomax et al 2011;Tong and Fu.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, we chose to implement a rest interval that was shorter than previous research as it better reflected practices during normal exercise settings. Others have found performance enhancements when engaging in the RWU 30 min before exercise [25,26]. The optimal rest interval between RWU and exercise remains unclear, but our findings, combined with previous research [25,26], suggest longer may be better than shorter.…”
Section: Performancesupporting
confidence: 51%
“…Others have found performance enhancements when engaging in the RWU 30 min before exercise [25,26]. The optimal rest interval between RWU and exercise remains unclear, but our findings, combined with previous research [25,26], suggest longer may be better than shorter. Secondly, the limitations of the RWU device precluded us from controlling and/or quantifying inspiratory pressure or flow rate during the RWU, meaning we could not standardize conditions between or within participants.…”
Section: Performancesupporting
confidence: 51%